1974
DOI: 10.1073/pnas.71.7.2787
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Effect of Heterochromatin on Chromosome Pairing

Abstract: Rye chromosomes were selectively stained in the meiosis of triticale (Secale L.). In triticale a varying number of homologous chromosomes fail to pair at meiosis and are seen as univalents at first mietaphase (1, 2). It has been suggested (3-7) that these univalents are mainly chromosomes of the rye genome. This conclusion was based on two general observations made on octaploid triticale. First, some triticales have a strong tendency to revert to hexaploids that resemble wheat (3). Second, individual chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…In hexaploid triticale (Thomas and Kaltsikes, 1974;Lelley, 1975b;Schiegel, 1978a;Jung and Lelley, 1985a, b;Jung et aL, 1985;Galindo and Jouve, 1989) and in wheat-rye addition lines (Schlegel, 1978b;Orellana et a!., 1984), rye Fominaya and Orellana (1988) demonstrated a phenomenon of interference between wheat and rye chromosomes as a cause of the decrease of rye-rye and wheat-wheat homologous pairing observed at metaphase I in triticale with respect to their corresponding rye and wheat parents.…”
Section: Chromosome Constitution and Modificationsmentioning
confidence: 99%
“…In hexaploid triticale (Thomas and Kaltsikes, 1974;Lelley, 1975b;Schiegel, 1978a;Jung and Lelley, 1985a, b;Jung et aL, 1985;Galindo and Jouve, 1989) and in wheat-rye addition lines (Schlegel, 1978b;Orellana et a!., 1984), rye Fominaya and Orellana (1988) demonstrated a phenomenon of interference between wheat and rye chromosomes as a cause of the decrease of rye-rye and wheat-wheat homologous pairing observed at metaphase I in triticale with respect to their corresponding rye and wheat parents.…”
Section: Chromosome Constitution and Modificationsmentioning
confidence: 99%
“…Thomas and Kaltsikes (1974) attributed the reduced pairing of the rye chromosomes, relative to wheat chromosomes in triticale, to the greater amount of heterochromatin in the rye chromosomes. On the other hand, Fominaya and Orellana (1988) found no relationship between the amount of heterochromatin in the rye chromosomes and reduction of pairing of chromosomes in octaploid triticales.…”
Section: Meiotic Behaviormentioning
confidence: 99%
“…At least in the first backcross hybrids ABRR and DUnRR the dosage of wheat and ventricosa genomes have been reduced with respect to the parental amphiploids (AABBRR, DDUnUnRR), and however the rye-rye homologous pairing is lower than in those amphiploids (table 1) (see Naranjo and Lacadena, 1982;Cermeño et al, 1985). Thomas and Kaltsikes (1974;1976) and Roupakias and Kaitsikes (1977) concluded that the presence of telomeric C-heterochromatin on rye chromosomes could be responsible for the rye meiotic irregularities observed in triticale and wheat-rye combinations, since heterochromatin is late replicating and therefore DNA replication of C-heterochromatin could interfere with meiotic prophase pairing. Nevertheless, this cannot explain our results because if the only cause of the decrease of the rye homologous pairing was the presence of telomeric C-blocks in the rye chromosomes, we would expect the same behaviour in the amphiploids as in the hybrids, and in the Ae.…”
Section: Homologous Pairingmentioning
confidence: 99%